Mapping the impact of crossbreeding in smallholder cattle systems in Indonesia - Widi, Tri Satya Mastuti (2015)
In response to increasing demand for meat, Indonesia’s government has been implementing crossbreeding with European beef breeds to improve the meat production of local cattle. The main objective of the present study was to evaluate the benefits and consequences of crossbreeding in smallholder cattle farming systems in Madura and Central Java. The study used participatory approaches, observations during cultural events in Madura, and measurements of cattle performances, feeding practices and farm inputs and outputs. In Madura, crossbreeding is not a threat to the two cultural events involving cattle, sonok (cow conformation contest) and karapan (bull racing), nor to the sub-populations of Madura cattle in the specific areas where these events are organised. Farmers outside the sonok and karapan areas, prefer Limousin crossbreds (madrasin) to conventional Madura cattle. The current breeding and conservation approaches do not distinguish between different Madura cattle types and do not consider the specific needs of the farmers in the sonok and karapan areas. In Java, farmers perceive that crossbreeding of Simmental with local Ongole cattle is beneficial for them. Crossbreeding was not accompanied with changes in the cattle farming systems. Crossbred cattle reached a higher body weight and therefore had a higher market price, but they also required more feed. This resulted in comparable Gross Margins for farms with crossbred and Ongole stock. Farmers preferred the crossbreds because of their nice appearance, high growth rate and the higher market price for progeny compared to Ongole. Crossbreeding as a tool of intensification did not reduce the carbon footprint and land use per kilogram liveweight produced. The advantage from the faster growth of crossbreds was counteracted by the higher emissions and land use from feed production for crossbreds. The dualism in crossbreeding is that policy makers promote crossbreeding to meet the increasing demand for beef, whereas farmers are concerned with their livelihoods and the multi-functionality of cattle. Crossbreeding contributes to increased meat production at the national level, however, it has limited possibilities to improve cattle production at farm level. Crossbreeding is also not reducing rural poverty. Participatory approaches should ensure that farmers’ views are considered in national crossbreeding policies and practices. In Madura and Central Java, farmers identified economic benefits, feed availability, cattle management, animal performances, additional functions of cattle, and health and fertility as issues to be considered beforehand in a genetic impact assessment of crossbreeding. Other stakeholders mentioned meat production, environmental quality and diversity in farm animal genetic resources as important issues. Crossbreeding will inevitably continue in Java and Madura. Breeding strategies, have to be adjusted, however, as farmers do not want to upgrade their local cattle to Simmental or Limousin. Viable populations of local cattle are needed to ensure sustainable crossbreeding strategies.